Indel patterns of the plastid DNA trnL- trnF region within the genus Poa (Poaceae) - Stoneberg Holt, Sierra Dawn; Horová, Lucie; Bures, Petr (Journal of plant research, 2004)
The use of insertion/deletion (indel) patterns from sequences of the trnL intron and trnL-F intergenic spacer (IGS) in finding plastid genome types of the genus Poa L. was studied. New sequences for 23 taxa ( P. alpina, P. badensis, P. bulbosa, P. crassipes, P. molinerii, P. annua, P. chaixii, P. granitica, P. pratensis, P. sibirica, P. remota, P. botryoides, P. cenisia, P. compressa, P. laxa, P. margilicola, P. media, P. nemoralis, P. palustris, P. pannonica, P. pirinica, P. riphaea, and P. sejuncta) and 18 previously published sequences, which represent 11 of the 13 sections listed for Poa in Flora Europaea, were investigated. Collections were made primarily in central Europe. Indel patterns, despite sampling less than 0.7% of the plastid genome, produced four taxa groupings that were congruent with the major divisions obtained in intensive, previously published restriction-site studies. Insertion/deletion events in the trnL intron and trnL-trnF IGS were in nearly all cases unique to a single pattern group and thus provided almost no information about relationships among these groups. Indels did, however, provide a meaningful infrageneric classification criterion for Poa. They can serve as useful tools in studying relationships within this genus.
Keywords: Base Sequence; plastidy; DNA, Plant; Poa; Genome, Plant; introny; Molecular Sequence Data; Introns; DNA primery; Phylogeny; molekulární sekvence - údaje; konsenzuální sekvence; Exons; sekvenční homologie nukleových kyselin; Consensus Sequence; Sequence Alignment; DNA rostlinná; Sequence Homology, Nucleic Acid; sekvence nukleotidů; Plastids; DNA Primers; exony; fylogeneze; genom rostlinný; sekvenční seřazení